Towards estimating brittleness index of the ECCA Group sandstones based on mineralogical characteristics - Sekgona, Tumi Lauretta (My University, 2025)
Brittleness is a critical property in geological formations, influencing the extraction and production processes in the oil and gas industry, as well as in mining and civil engineering applications. Many methods were developed to determine the brittleness index; however, none is standardised. This study aims to estimate the brittleness index of the Ecca Group Sandstones, a significant geological formation in southern Africa, based on its mineralogical characteristics. Petrographic analysis, including thin section microscopy and image analysis, was conducted to quantify petrographic characteristics such as mineral composition, grain size distribution, and fabric properties (packing density, packing proximity, consolidation factor). Through detailed petrographic analysis, key mineralogical parameters, including the types and proportions of clay minerals, quartz, feldspars, and other constituents, were systematically evaluated. Statistical analyses, including correlation studies and multivariate analyses, were conducted to establish relationships between these petrographic attributes and the Brittleness Index. Results indicate that specific petrographic characteristics such as contact type and contact nature strongly influence the brittleness of the sandstones in the Ecca Group. Four brittleness indices, namely B3, B4, B5, and B6, were formulated. Brittleness indices B1 and B2 proved ineffective, hence equations were not formulated for them. Models with a high number of independent variables are deemed impractical and less reliable. Hence, among the developed models for predicting brittleness indices, the most optimal choice is the model that has fewer independent variables, along with higher values of R2a and F. These brittleness indices (B3, B4, B5 and B6) highlight the complex interplay of various contact types and packing arrangements in determining the brittleness of a material
Thesis (M. Sc. (Geology)) -- University of Limpopo, 2025
Keywords: Brittleness index; Petrographic characteristic; Sandstone; Ecca Group; Hydraulic fracturing, Southern Africa; Petrographic microscope; Hydraulic fracturing; Brittleness